Neuroblastoma-like schwannoma in a case of schwannomatosis: Report of a rare case - Sulhyan, Kalpana R; Deshmukh, Bhakti D; Gosavi, Alka V; Ramteerthakar, Nayan A (International Journal of Health Sciences, 2015)
Â Â Â Schwannomatosis is a term used to describe patients with multiple nonvestibular schwannomas with no other stigmata of neurofibromatosis type-2 (NF2). Neuroblastoma-like schwannoma is a rare subtype of schwannoma, with histological features resembling a neuroblastoma. This case is probabaly the second case of very uncommon neuroblastomaâ€like schwannoma, in a patient of schwannomatosis. Â